(untitled) (Scientific journal of the Fergana State University, 2025)
The fact that all the processes of entering the child’s psyche slowly and precisely through the means of communication paves the way for the child to master language skills such as understanding the literary language and speaking correctly. This and similar aspects are disclosed in the article.